2014
DOI: 10.4103/1119-3077.141427
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of compliance to iron supplementation among pregnant women in Enugu, Southeastern Nigeria

Abstract: The compliance rate of 65.9% for iron supplementation by pregnant mothers in Enugu can further be improved by providing the drug free of charge in the short term and improvement in education and socioeconomic class of the populace in the long run.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
64
10
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 14 publications
(31 reference statements)
15
64
10
5
Order By: Relevance
“…Indeed, in our study 74.1% of women who had this level of education had respected the appropriate duration of iron consumption and were 2.49 times more likely to respect it. Corresponding findings were found in Nepal [18] with an OR of 3.1, Nigeria [21] with an OR of 5.5 and Pakistan [25] with OR of 2.36. These results are similar to previous studies in the DHS where the authors found that women with a high level of education were likely to consume iron properly [8] [9]…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Indeed, in our study 74.1% of women who had this level of education had respected the appropriate duration of iron consumption and were 2.49 times more likely to respect it. Corresponding findings were found in Nepal [18] with an OR of 3.1, Nigeria [21] with an OR of 5.5 and Pakistan [25] with OR of 2.36. These results are similar to previous studies in the DHS where the authors found that women with a high level of education were likely to consume iron properly [8] [9]…”
Section: Discussionsupporting
confidence: 61%
“…This low proportion has also been found in several developing countries such as Cambodia, Mali, Nepal and Indonesia, where they are respectively 47%, 28%, 20.7% and 40% [17] [18] [19] [20]. However, relatively high rates have also been observed in other developing countries such as Nigeria [21] and India [22] where the authors reported rates of 65.9% and 64.7%, respectively. In Europe, studies of pregnant English women indicated that 70% of these women adhered to iron supplementation [23] [24].…”
Section: Discussionmentioning
confidence: 86%
“…5 Another study conducted in Enugu , Southeastern Nigeria Ugwu, et al in which the major barriers to compliance to iron supplementation was gastrointestinal side effects of iron supplements (41.7%), non-affordability of iron supplements (28.3% ) and forgetfulness (15%). 6 The study shows that the incidence of anemia among subject who did not comply with the supplementation was significantly higher compared to complaint. 13% of pregnant women who did not comply with the supplementation were having anemia (p value <0.001).…”
Section: Discussionmentioning
confidence: 94%
“…16 The major problem with iron supplementation in pregnancy is compliance and this is thought to be a potential driver to the persistent high prevalence of anemia in this population.…”
mentioning
confidence: 99%